A role for autonomic cardiac control in the effects of oxytocin on social behavior and psychiatric illness - Quintana, Daniel S.; Kemp, Andrew H.; Alvares, Gail A.; Guastella, Adam J. (Frontiers in Neuroscience, 2013)
Cumulative evidence over the last decade indicates that intranasally administered oxytocin (OT) has a major impact on social behavior and cognition. In parallel, researchers have also highlighted the effects of OT on cardiovascular and autonomic nervous system regulation. Taken at face value, these two streams of research appear largely unrelated. However, another line of evidence highlights a key role for autonomic cardiac control in social behavior and cognition. In this review, we suggest that autonomic cardiac control may moderate the relationship between OT and social behavior. We also highlight the importance of autonomic cardiac control in psychiatric disorders of social dysfunction and suggest that heart rate variability (HRV) – an index of autonomic cardiac control – may play a key role in patient response in treatment trials of OT.